Predicting the impact of urban area security initiative funding on terrorist incidents in the United States - Nash, Rebecca M. (Criminology, criminal justice, law & society, 2017)
The terrorist attacks on September 11, 2001 are the most devastating terrorist events to occur within the borders of the United States with almost 3,000 deaths, 6,000 injured, and close to 2 trillion dollars in damage. This tragedy impelled the United States government to create the Department of Homeland Security, the governmental body that oversees the myriad of counter-terrorism measures implemented since 9/11, including the Urban Areas Securities Initiative, which is responsible for preventing and responding to future terrorist incidents. This study utilizes descriptive, forecast, and intervention time series analyses to define trends in terrorism from 1970 to 2010, to forecast terrorist events in 2011 and 2012, and to test the effectiveness of the UASI in preventing future terrorist attacks. Descriptive and forecast time series analyses findings reveal an overall downward trend in terrorist attacks in the seven urban areas examined in this study with the Los Angeles/Long Beach Urban area and New York City having the highest-risk of possible terrorist attacks in the future. Intervention analyses reveal that for all seven urban areas examined, the UASI program is statistically insignificant in influencing the number of terrorist incidents since its implementation in 2003.